KCNQ2 Encephalopathy and Neonatal Seizures - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 2011)
Researchers from centers in Belgium and Australia analyzed 80 patients with unexplained neonatal or early infantile seizures and associated psychomotor retardation for KCNQ2 mutations.